Development of Preventive Vaccines for Hepatitis C Virus E1/E2 Protein - Faezeh Ghasemi; Majid Ghayour Mobarhan; Hamed Gouklani; Zahra Meshkat (Iranian Society of Pathology, 2018)
Hepatitis C virus (HCV) is responsible for a vast majority of liver failure cases. HCV is a kind of blood disease appraised to chronically infect 3% of the worlds' population causing significant morbidity and mortality. Therefore, a complete knowledge of humoral responses against HCV, resulting antibodies, and virus-receptor and virus-antibody interactions, are essential to design a vaccine. HCV epitopes or full sequence of HCV proteins can induce HCV specific immune responses. In fact, structural proteins are usually the main target of humoral responses and non-structural proteins are usually the main target of cellular responses. Hence, various vaccines based on distinct antigenic combinations are developed to prevent HCV infection and the current study tried to summarize them.